Digital anthropology - Horst, Heather A.; Miller, Daniel, 1954- (London ; New York : Routledge, 2020)
"Anthropology has two main tasks: to understand what it is to be human and to examine how humanity is manifested differently in the diversity of culture. These tasks have gained new impetus from the extraordinary rise of the digital. This book brings together several key anthropologists working with digital culture to demonstrate just how productive an anthropological approach to the digital has already become. Through a range of case studies from Facebook to Second Life to Google Earth, Digital Anthropology explores how human and digital can be defined in relation to one another, from avatars and disability; cultural differences in how we use social networking sites or practise religion; the practical consequences of the digital for politics, museums, design, space and development to new online world and gaming communities. The book also explores the moral universe of the digital, from new anxieties to open-source ideals. Digital Anthropology reveals how only the intense scrutiny of ethnography can overturn assumptions about the impact of digital culture and reveal its profound consequences for everyday life. Combining the clarity of a textbook with an engaging style which conveys a passion for these new frontiers of enquiry, this book is essential reading for students and scholars of anthropology, media studies, communication studies, cultural studies and sociology."--Publisher's website.
Section A: Introduction. The Digital and The Human / Daniel Miller and Heather A. Horst. -- Section B: Positioning Digital Anthropology. Rethinking 'Digital' Anthropology / Tom Boellstorff ; New Media Technologies in Everyday Life / Heather A. Horst ; Geomedia: the Reassertion of Space Within Digital Culture / Lane DeNicola. -- Section C: Socialising Digital Anthropology. Disability in the Digital Age / Faye Ginsburg ; Approaches to Personal Communication / Stefana Broadbent ; Social Networking Sites / Daniel Miller. -- Section D: Politicising Digital Anthropology. Digital Politics and Political Engagement / John Postill ; Free Software and the Politics of Sharing / Jelena Karanovic ; Diverse Digital Worlds / Bart Barendregt ; Digital Engagement: Voice and Participation in Development / Jo Tacchi. -- Section E: Designing Digital Anthropology. Digital Anthropology in Design Anthropology / Adam Drazin ; Museum Digital = ? / Haidy Geismar ; Digital Gaming, Game Design, and its Precursors / Thomas Malaby.
Includes bibliographical references and index.
BIGD
amazon.co.uk
Keywords: Mass media and anthropology; Digital media -- Social aspects; Digital communications -- Social aspects; Communication in anthropology; Mass media and culture